Trend analysis of seasonal and annual precipitation in Inner Mongolia - Shaoxin GAO; Jing LIU; Yu CHANG (暴雨灾害, 2022)
Using precipitation data at 110 national stations during 1970 to 2019 in Inner Mongolia and based on empirical orthogonal function (EOF) analysis method, rescaled range analysis (R/S) and non-periodic cycle analysis, the values of Hurst parameter H, fractal dimension D and non-cycle average cycle length of seasonal and annual precipitation in Inner Mongolia were calculated. Then the variation trends and memory cycles of precipitation at the time series were analyzed. The results show that: (1) The annual precipitation slightly increases. Among regions, the increasing trend of precipitation is the most significant in the east about eastern region of Inner Mongolia. The change trend has a persistent feature, lasting for 8 years. But, there has a decreasing trend in the south about western region and individual areas of the east region. (2) The precipitation in spring, autumn and winter shows an increasing trend, while the precipitation in summer shows a decreasing trend. Especially, the increase is the most obvious in the individual north area about eastern region where H equals 1. It presents the characteristics of a complete prediction, and the future trend of precipitation is increasing. Furthermore, this passes 95% significance test. (3) The past increment of precipitation in the four seasons is positively correlated with the future increment. The persistence of the decreasing trend of precipitation in summer is the weakest, and the increasing trend of precipitation in winter is the strongest. The memory length of spring, summer, autumn and winter is 8 years, 8 years, 9 years and 10 years, respectively.